Effects of Assault Type on Cognitive Behaviour Therapy for Coexisting Depression and Alcohol Misuse - Kylie A. Bailey (Journal of Clinical Medicine, 2017)
Although assault exposure is common in mental health and substance misusing populations, screening for assaults in treatment settings is frequently overlooked. This secondary analysis explored the effects of past sexual (SA) and physical (PA) assault on depression, alcohol misuse, global functioning and attrition in the Depression and Alcohol Integrated and Single focussed Intervention (DAISI) project, whose participants (N = 278) received cognitive behaviour therapy (CBT) for their depression and/or alcohol misuse. Of the 278 DAISI participants, 220 consented to screening for past assault (either by a stranger or non-stranger) at baseline. Depression, alcohol, and global functioning assessments were administered at baseline and 3, 12, 24, and 36 months post baseline. A between-group analysis was used to assess differences between SA and No SA, and PA and No PA groupings, on adjusted mean treatment outcomes across all assessment periods. SA and PA participants had similar mean symptom reductions compared to No SA and No PA participants except for lower depression and global functioning change scores at the 12-month follow-up. People with coexisting depression and alcohol misuse reporting SA or PA can respond well to CBT for depression and alcohol misuse. However, follow-up is recommended in order to monitor fluctuations in outcomes.